Design of Intelligent Agriculture Management Information System Based on IoT - Duan Yan-e (2011 International Conference on Intelligent Computation Technology and Automation, 2011)
Agricultural information technology (AIT) has been broadly applied to every aspect of agriculture and has become the most effective means & tools for enhancing agricultural productivity and for making use of full agricultural resources. As an important sub-technology of AIT, the using of technology of Agriculture Information Management directly affects the degree of agricultural informatization and efficiency of agricultural production's decision. In this paper, on the basis of introducing the concept of agricultural information management and analyzing the features of Agricultural data, the designing method and architecture of Intelligent Agriculture MIS was discussed in detail, finally, this paper gives an implementation example of system in agricultural production.